MODEL DESTINASI MICE AGROWISATA GUNUNG MAS BOGOR - Firman Syah; Dewi Winarni Susyanti; Imam Syafganti (Bisnis Event, 2023)
At present, MICE destinations have become an attraction and are expected to increase foreign exchange in tourism. The Ministry of Tourism and the National Development Planning Agency (Bappenas) now also support the core business of tourism. Because when MICE can be developed, it will gain seven times the profit compared to tourism which is merely entertainment. Especially in Indonesia, MICE activities are still minimal. Bogor Regency as a destination with tourist attractions also has the opportunity to develop MICE, call it the Gunung Mas Agrotourism. Under the management of PT Perkebunan Nusantara (PTPN) VIII, Gunung Mas Agrotourism is now able to provide a variety of activities according to market needs. What are the MICE attractions that can be used for MICE tourism activities? How to maximize MICE destination in Gunung Mas Bogor Agrotourism? Results of research with qualitative methods explain that in Gunung Mas have tea walk potential and often hold formal meetings, weddings, and other activities on demand. Including important meetings which are scheduled in private. In fact, several times held a seminar. For this reason, there are four halls with various capacities that can accommodate 50 people, 100 people, even 300 people.